ANALISIS TINGKAT PENERIMAAN KOPI TAHLIL SEBAGAI KULINER KEARIFAN LOKAL : PERSPEKTIF GENERASI MILENIAL - Titi Rahayu Prasetiani Rahayu Prasetiani; Catur Ragil Sutrisno; Tsamara (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Tahlil coffee is a typical Pekalongan coffee made from coffee beans mixed with variousspices. The millennial generation has a lifestyle of socializing while drinking coffee. Thisstudy aims to examine coffee tahlil as a local culinary, whether it can be accepted by themillennial generation amidst the many choices of various other types of coffee. Theresearch was conducted using a survey approach, which involved the millennialgeneration as respondents. The technical analysis uses descriptive analytical techniquesto explain the level of acceptance of tahlil coffee based on coffee quality attributes amongthe millennial generation. Coffee tahlil has been accepted by the millennial generation.Coffee tahlil products as a whole are close to good, with a score range of 4-1, the averageproduct attribute has a score of 2.93. This product attribute score is above the averagevalue of 2.5. The taste of spices in the tahlil coffee, the aroma and suitability of the size ofthe tahlil coffee have been well appreciated, with a score above 3. Whereas what needsattention is the thickness and variety of servings which are at the bottom score.